Cognitive grammar : - Langacker, Ronald W (Oxford University Press, 2008)
This introductory text draws together and refines the descriptive and theoretical aspects of cognitive grammar. In a unified manner, it accomodates both the conceptual and the social-interactive basis of linguistic structure, as well as the need for both functional explanation and explicit structural description.